Optimasi Distribusi Koran Menggunakan Metode Saving Matriks (Studi Kasus : PT. Riau Pos Intermedia) - Sri Basriati; Rio Sunarya (UIN Sultan Syarif Kasim Riau, 2015)
Facing globalization era publishment of newspaper entrepreneur world demanded to be more competitive to fulfil consumen request. Process of distribution is strongly needed to be attended. One of important operational decision in process of distribution is determination delivery route can be categorize as Capacitated Vehicle Routing Problem (CVRP). It can be accomplished by using exact optimazition like integer programming. But in finishing need computation that very long time. Solving problem alternative method CVRP that easier is saving matrix. saving matrix conducted by making a matrix called by saving matrix. It contains list of saving acquired when coumpounding 2 consumens in 1 vehicle. Next make a row of consument by using 1 of farthest inserts, inserts cheapest, nearest neighbor and nearest insert metodh giving shortest space. Based on research gained 2 route newspaper distribution Riau pos and result of comparison row consumen show that cheapest method result shortest space is 1,646.067 km.Keywords: CVRP, cheapest, farthest, nearest, neighbour.